2019
DOI: 10.5935/1518-0557.20190030
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy in left ovary and contralateral uterine tube diagnosed one week apart in In Vitro Fertilization with donor eggs: Case report

Abstract: Bilateral ectopic pregnancy is a rare clinical condition with an estimated prevalence of 1/200 000 in spontaneous pregnancies. Studies have found that In Vitro Fertilization (IVF) is related to ectopic pregnancy independently, but the incidence of tubal disease in the donor egg recipient population is thought to be significantly lower than in the standard IVF population. We report the case of a patient participating in the egg-sharing program, who was diagnosed with ovarian ectopic pregnancy, treated with surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…ART was observed as a major risk factor in this case, as shown in Supplementary Table S1 . This was consistent with three previous reports (M Sueldo et al, 2014 ; Eom et al, 2018 ; Trindade et al, 2019 ). Among these, M Sueldo et al and Trindade et al reported concurrent OP and TP after the transfer of two fresh embryos, and Eom et al reported a patient who had undergone IUI treatment.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…ART was observed as a major risk factor in this case, as shown in Supplementary Table S1 . This was consistent with three previous reports (M Sueldo et al, 2014 ; Eom et al, 2018 ; Trindade et al, 2019 ). Among these, M Sueldo et al and Trindade et al reported concurrent OP and TP after the transfer of two fresh embryos, and Eom et al reported a patient who had undergone IUI treatment.…”
Section: Discussionsupporting
confidence: 94%
“…Combined pregnancy is rare and poses early diagnostic challenges. In existing reports, the clinical features of OP and TP patients have been unspecific, thus posing a dilemma for rupture and massive intra-abdominal bleeding with delayed diagnosis ( Trindade et al, 2019 ). Particularly in cases of OP, pre-operative diagnosis is difficult to perform; however, this situation is improving owing to recent advances in ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy was confirmed by HCG concentrations in 50%, unknown in 43%, but negative in 2 cases (2%). (19,20) Rare cases were one woman with a bilateral ovarian pregnancy (21), another with a left ovarian pregnancy diagnosed 3 weeks after left salpingectomy for tubal pregnancy after ovulation induction (22), 2 women with a tubal pregnancy and an ovarian pregnancy on the other side (23,24) and 6 ovarian pregnancies associated with an intrauterine pregnancy (heterotopic pregnancy), 2 of them spontaneously (25,26), 1 after ovulation induction ( 27), 1 after IUI (28) and 2 with IVF (14,29). In 5 of them, the intrauterine pregnancies continued uneventfully after the excision of the ovarian pregnancy.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…2 Previous reports of dual ovarian and tubal ectopic pregnancies in the literature are rare, and most case reports described their occurrence following ovarian induction. [3][4][5][6][7] Risk factors for extrauterine pregnancies include previous ectopic pregnancy, history of surgical manipulation of the tubes, genital infections, infertility and assisted reproductive technology (ART). 8,9 Our patient had no history of ovulatory stimulation and only reported a remote history of chlamydia infection.…”
Section: Discussionmentioning
confidence: 99%